How establishing a marine protected area network has shaped community and citizen science along California’s coast - Harwell, Todd A.; Meyer, Ryan M.; Ballard, Heidi L. (Frontiers in Marine Science, 2025)
Community and citizen science (CCS), the involvement of non-professional scientists in research and monitoring, has emerged as a key approach in tackling marine conservation issues. This has been evidenced especially in various monitoring efforts of marine protected areas (MPAs) with increasing involvement of CCS programs in contributing data used by MPAs in their adaptive management processes. Having recently engaged in its decadal management review process, this study focuses on the implementation of California’s MPA Network through an examination of the diverse impacts to CCS programs. Through an analysis of survey and interview data provided by leaders representing 12 CCS programs in addition to 13 members of the MPA State Leadership Team, we report on the varied impacts to a diverse set of CCS programs and explore how the relationships between MPAs and CCS in California have evolved over the past 10+ years. We found that regardless of State funding eligibility or receipt to participate in MPA monitoring, all 12 CCS program leaders reported overall increases or growth to their programs across all six focal impact type categories (participants, data, programmatic elements, finances/funding, and staff/partners). Additionally, MPA leaders shared perspectives on the evolving role of CCS, emphasizing the importance of collaboration and data alignment. These findings suggest that continued support for the collaborative MPA-CCS relationships could yield further mutual benefits for both the growing use and utility of CCS and its role in MPA implementation and marine conservation more broadly.